Effect of exercise intensity and volume on persistence of insulin sensitivity during training cessation - Bajpeyi, Sudip; Tanner, Charles J.; Slentz, Cris A.; Duscha, Brian D.; McCartney, Jennifer S.; Hickner, Robert C.; Kraus, William E.; Houmard, Joseph A. (East Carolina University, 2009)
Effect of exercise intensity and volume on persistence of insulin sensitivity during training cessation. J Appl Physiol 106: 1079â 1085, 2009. First published February 5, 2009; doi:10.1152/japplphysiol.91262.2008. The purpose of this study was to determine whether exercise prescriptions differing in volume or intensity also differ in their ability to retain insulin sensitivity during an ensuing period of training cessation. Sedentary, overweight/obese subjects were assigned to one of three 8-mo exercise programs: 1) low volume/moderate intensity [equivalent of 12 miles/wk, 1,200 kcal/wk at 40-55% peak O2 consumption (VO2peak), 200 min exercise/wk], 2) low volume/vigorous intensity (12 miles/wk, 1,200 kcal/wk at 65-80% VO2peak, 125 min/wk), and 3) high volume/vigorous intensity (20 miles/wk, 2,000 kcal/wk at 65-80% VO2peak, 200 min/wk). Insulin sensitivity (intravenous glucose tolerance test, SI) was measured when subjects were sedentary and at 16-24 h and 15 days after the final training bout. SI increased with training compared with the sedentary condition (P less than or equal to 0.05) at 16-24 h with all of the exercise prescriptions. SI decreased to sedentary, pretraining values after 15 days of training cessation in the low-volume/vigorous-intensity group. In contrast, at 15 days SI was significantly elevated compared with sedentary (P less than or equal to 0.05) in the prescriptions utilizing 200 min/wk (low volume/moderate intensity, high volume/vigorous intensity). In the high-volume/vigorous-intensity group, indexes of muscle mitochondrial density followed a pattern paralleling insulin action by being elevated at 15 days compared with pretraining; this trend was not evident in the low-volume/moderateintensity group. These findings suggest that in overweight/obese subjects a relatively chronic persistence of enhanced insulin action may be obtained with endurance-oriented exercise training; this persistence, however, is dependent on the characteristics of the exercise training performed.
Keywords: Obesity; Physical activity; Cardiovascular Diseases; Metabolic syndrome